PENINGKATAN KUALITAS TIDUR BAYI DENGAN TREATMENT BABY SPA - Haerani; Jusni; Anggi Ashari; Dahlia Melandani (JMNS, 2019)
Sleep is one of the factors that affect a baby's growth. Improving the quality of baby's sleep can be done through massage by parents. The purpose of this study was to determine the improvement of baby's sleep quality with baby spa treatment. The research method used in this study was pre-experimental with a pretest posttest one group design approach. This research was conducted at the independent practice midwife A. Tenri, Bulukumba Regency. In this study, the population was the baby's mother, totaling 30 babies using the total population sampling technique. The results of this study are that there is an effectiveness of baby massage on improving the quality of baby sleep as evidenced by respondents who experienced an increase in sleep quality, most (73.33%) of respondents had good sleep quality.